United States Government-Supported Family Planning and Reproductive Health Outreach in the Democratic Republic of the Congo: Lessons Learned and Recommendations [Corrigendum] - Ibrahimi S; Youssouf B; Potts C; Dumouza A; Duff R; Malaba LS; Brunner B (Dove Medical Press, 2024)
Ibrahimi S, Youssouf B, Potts C, et al. Open Access J Contracept. 2024 Mar 5:15:13–21. Our authors have updated this article to include a disclaimer statement in the “Funding” section on page 20 of the published paper. The funding statement should read as follows. Funding This research was funded by United States Agency for International Development (USAID) in accordance with the USAID Integrated Health Program. Contract No: AEP-C-72066018C00001. This journal article is made possible by the support of the American People through USAID. The authors’ views do not necessarily reflect the views of USAID. The authors apologize for any inconvenience caused to the readers.